Synthesis, characterization, and cancer cell-selective cytotoxicity of mixed-ligand cobalt(iii) complexes of 8-hydroxyquinolines and phenanthroline bases - Deka B.; Sarkar T.; Bhattacharyya A.; Butcher R.J.; Banerjee S.; Deka S.; Saikia K.K.; Hussain A. (My University, 2025)
Transition metal complexes exhibiting selective toxicity towards a broad range of cancer types are highly desirable as potential anticancer agents. Herein, we report the synthesis, characterization, and cytotoxicity studies of six new mixed-ligand cobalt(iii) complexes of general formula [Co(B)2(L)](ClO4)2 (1-6), where B is a N,N-donor phenanthroline base, namely, 1,10-phenanthroline (phen in 1, 2), dipyrido[3,2-d:2′,3′-f]quinoxaline (dpq in 3, 4), and dipyrido[3,2-a:2′,3′-c]phenazine (dppz in 5, 6), and L is the monoanion of 8-hydroxyquinoline (HQ in 1, 3, 5) and 5-chloro-7-iodo-8-hydroxyquinoline (CQ in 2, 4, 6). The X-ray single crystal structures of complexes 1 and 2 as PF6− salts revealed a distorted octahedral CoN5O coordination environment. Complexes demonstrated good stability in an aqueous buffer medium and in the presence of ascorbic acid as a reductant. Cytotoxicity studies using a panel of nine cancer cell lines showed that complex 6, with the dppz and CQ ligands, was significantly toxic against most cancer cell types, yielding IC50 values in the range of 2 to 14 μM. Complexes 1, 3, and 5, containing the HQ ligand, displayed lower toxicity compared to their CQ counterparts. The phenanthroline complexes demonstrated marginal toxicity towards the tested cell lines, while the dpq complexes exhibited moderate toxicity. Interestingly, all complexes demonstrated negligible toxicity towards normal HEK-293 kidney cells (IC50 > 100 μM). The observed cytotoxicity of the complexes correlated well with their lipophilicities (dppz > dpq > phen). The cytotoxicity of complex 6 was comparable to that of the clinical drug cisplatin under similar conditions. Notably, neither the HQ nor the CQ ligands alone demonstrated noticeable toxicity against any of the tested cell lines. The Annexin-V-FITC and DCFDA assays revealed that the cell death mechanism induced by the complexes involved apoptosis, which could be attributed to the metal-assisted generation of reactive oxygen species. Overall, the dppz complex 6, with its remarkable cytotoxicity against a broad range of cancer cells and negligible toxicity toward normal cells, holds significant potential for cancer chemotherapeutic applications. © 2024 The Royal Society of Chemistry